India's development cooperation - opportunities and challenges for international development cooperation - Vijaya Katti; Tatjana Chahoud; Atul Kaushik (Deutsches Institut für Entwicklungspolitik (DIE), 2009)
India has been a provider of development assistance since its independence, but its role and contribution has gained momentum more recently as a result of its growing economic and political influence in the global community. In contrast to OECD/DAC countries until today India do not have any publicly declared policy paper or standards. The guiding principles for its foreign policy and its development cooperation are founded in the Panchsheel/ Bandung Principles. According to this approach India's development cooperation is implemented by various ministries and institutions with the Ministry of External Affairs (MEA) as the leading ministry. As India does not have a single agency for Indian Development Cooperation (IDC), estimates about the magnitude of India's development assistance have to be culled out of the budget outlays of the relevant Ministries/ Departments and other sources. According to available data India's aid focuses first on neighbouring countries, followed by African countries. In recent years India became an important actor in promoting regional integration. Main instruments were trade relations and increased investment in regional infrastructure. Since 2002 India also played a significant role in the reconstruction of Afghanistan. In addition India is strengthening its ties with Africa through lines of credit, foreign direct investment (FDIs), and technical assistance. Considerably, India continues to be the largest contributor to peace keeping missions in Africa. Besides the expected benefits from India's development cooperation for African countries there also remain some challenges and risks. India's development cooperation policy approach is clearly distinct from the OECD/DAC approach, the principles of non-interference and mutual respect for sovereignty remaining major features. However there are also some rethinking and discussions going on about the need for improved databases and for aid indicators as well as dialogues with traditional donors, India's participation in the Heiligendamm Process being a case in point.
Keywords: 330